Design of solar power system for the new mini region of broadband seismometer shelter in Tiganderket, Karo, North Sumatera, Indonesia. (December 2020) - Sinambela, Marzuki; Situmorang, Marhaposan; Tarigan, Kerista; Humaidi, Syahrul; Rahayu, Teguh
Abstract: The solar power installation on a new broadband seismometer shelter will greatly be affected by the quality of waveform data. The lower power means a physically smaller footprint and a less costly installation for a new station which must be located far from the main power system. In this case, we have installed the solar power system in the new broadband seismometer shelter in the mini region at TKSM station, in Tiganderket, Karo, North Sumatera Indonesia. The main goal of this study, to design, testing the solar cell, and compute the power spectral after installation of the power cell in the new shelter, which located away from roads and cities and human activity. The results presented that the good performance of the solar power system (solar cell, solar charge controller, and battery) for continuous transmission and to collect the waveform data based on the performance TKSM station using power spectral density function methods.